FEAR OF MISSING OUT SEBAGAI PREDIKTOR KECEMASAN PADA REMAJA: STUDI CROSS-SECTIONAL - Susi Muryani; Nurhakim Yudhi Wibowo ((IJP) Indonesia Jurnal Perawat, 2026)
Fear of Missing Out (FOMO) is an emerging psychosocial phenomenon among adolescents associated with intensive social media use, with prevalence reaching 50–60% in Indonesia. This condition contributes to mental health problems, particularly anxiety, which increased 41% during 2020–2023.  Objective the study to analyze the relationship between FOMO and anxiety levels in adolescents. A quantitative study with cross-sectional design was conducted in Tegal City, Central Java, from January to March 2026. The sample consisted of 87 adolescents aged 13–18 years selected through total sampling technique. Research variables included FOMO (independent), anxiety level (dependent), and gender (characteristic). FOMO was measured using the FOMO-12 scale (α=0.85) and anxiety using DASS-21. Univariate analysis (frequency distribution, percentage, mean ± SD, median) and bivariate analysis using chi-square test with significance level p0.05 were conducted. The result showed the majority of respondents were female (80.5%). Most experienced mild FOMO (60.9%) and normal anxiety (80.5%). Chi-square test showed a significant relationship between FOMO and anxiety level (χ²=30.07; p=0.001). Adolescents with severe FOMO had 92 times higher odds of experiencing abnormal anxiety compared to those without FOMO (95% CI: 7.32–1156.86). The Conclusion that FOMO is significantly associated with increased anxiety in adolescents, particularly in the severe FOMO category. Promotive and preventive efforts regarding healthy social media use need to be strengthened among adolescent groups through routine screening for FOMO and anxiety in community health centers and schools, as well as evidence-based digital literacy education.